1993
DOI: 10.1111/j.1469-8137.1993.tb03787.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of protein patterns in non‐mycorrhizal and vesicular–arbuscular mycorrhizal roots of red clover

Abstract: SUMMARYA comparison of the protein content and patterns in root extracts from non-mycorrhizal and vesicular-arbuscular mycorrhizal [Glomus mosseae (Nicol. et Gerd.) Gerd. et Trappe] red clover {Trifolium pratense L.) has been made. Soluble protein content was higher in mycorrhizal than in non-mycorrhizal roots. After separation by DEAEcellulose chromatography and electrophoretic analysis, several additional polypeptides appeared in mycorrhizal extracts. In addition, it seems that one of the additional proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 30 publications
0
17
1
5
Order By: Relevance
“…During the time of infection, an increase was obvious for some low MW polypeptides called Pi (16,19,23, biosis are associated with modifications in gene expression in both symbionts (Dumas et al, 1989;Dumas-Gaudot et al, 19946;Gianinazzi-Pearson et al, 1994;Gianinazzi et al, 1995;GianinazziPearson, 1995;Kapulnike^a/., 1996;Murphy et al, 1997). Accumulation of additional polypeptides has already been reported in AM roots of several plants (Dumas et al, 1989;Wyss et al, 1990;Arines et al, 1993;Garcia-Garrido et al, 1993;Dumas-Gaudot et al, 19946;Simoneau et al, 1994). Endomycorrhizins (Wyss et al, 1990) designate SRpolypeptides observed in AM.…”
Section: Up and Down Regulation Of Preexisting Polypeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the time of infection, an increase was obvious for some low MW polypeptides called Pi (16,19,23, biosis are associated with modifications in gene expression in both symbionts (Dumas et al, 1989;Dumas-Gaudot et al, 19946;Gianinazzi-Pearson et al, 1994;Gianinazzi et al, 1995;GianinazziPearson, 1995;Kapulnike^a/., 1996;Murphy et al, 1997). Accumulation of additional polypeptides has already been reported in AM roots of several plants (Dumas et al, 1989;Wyss et al, 1990;Arines et al, 1993;Garcia-Garrido et al, 1993;Dumas-Gaudot et al, 19946;Simoneau et al, 1994). Endomycorrhizins (Wyss et al, 1990) designate SRpolypeptides observed in AM.…”
Section: Up and Down Regulation Of Preexisting Polypeptidesmentioning
confidence: 99%
“…Frisson (myc"^, nod"^) (Samra and tobacco (Dumas et al, 1989;Pacovsky, 1989;et al, 1996a). However, discrimination between Schellenbaum, Gianinazzi & Gianinazzi-Pearson, symbiosis-related (SR) polypeptides and fungal 1992; Arines, Palma & Vilarino, 1993, Garcia-polypeptides was still difficult, owing to the fact that Garrido, Toro & Ocampo, 1993; Dumas-Gaudot et the fungal partner of the AM symbiosis is a true al., 19946). The accumulation of new polypeptides symbiont which has a very limited growth without in AM symbiosis was also demonstrated in RiT-the host roots (Becard, Douds & Pfeffer, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In tomato roots with proteins separated exclusively by native PAGE it was similarly possible to detect three constitutive chitinase isoforms and one isoform that were shown to be induced by Glomus intraradices colonization [35]. In order to improve electrophoresis resolution, protein extracts from mycorrhizal roots of red clover were fractionated by ion exchange chromatography before SDS-PAGE [36]. Roots were ground in liquid nitrogen and the resulting powder was homogenized in K-phosphate buffer, and polyvinylpolypyrrolidone (PVPP) and ascorbic acid were added to the lysis buffer toavoid interference caused by phenolic compounds and oxidizing agents present within the sample.…”
Section: Protein Separation Methods: Improving Resolutionmentioning
confidence: 99%
“…Compounds that could interfere with cchromatography were removed in an extra clean-up step by precipitating proteins with ammonium sulfate saturations, and salts were removed by dialysis from the precipitates. Proteins were then vacuum concentrated and ressolubilized [36]. Chromatography was used for subsequent analysis of the fractions through two independent separation methods, isoelectric focusing (IEF) and SDS-PAGE.…”
Section: Protein Separation Methods: Improving Resolutionmentioning
confidence: 99%
“…Arines et al, (1993) also detected two to six fold increases in soluble proteins in mycorrhizal clover roots. Zinc nutrition also enhanced the accumulation of soluble proteins in mycorrhizal plants which may be due to the fact that Zn is responsible for the synthesis of amino acids such as tryptophan and asparagine.…”
Section: Soluble Proteinsmentioning
confidence: 96%